Faktor Penentu Terhadap Perilaku Remaja Putri Pada Masa Pubertas - Putri, Yelmi Reni; Suryani, Wangi; Dewi, Sri (REAL in Nursing Journal, 2021)
Background: Puberty refers to the ripening of reproductive organs characterized by the first menstruation in young women (menarche), according to observation data made to young women they feel embarrassed by the changes in physical form that occur at puberty when there is already acne they are not confident, breasts begin to enlarge they fret because they have to wear longer clothes. The purpose of the study was to identify the behavior of young women during puberty in Luak Subdistrict. Methods:This study is Desciptive Analytics with Cross Sectional Study approach. The instrument used is a quisioner and is processed using computerization with the Chi-Square statistical test. The study was conducted on 71 respondents. Results: This study were obtained by 44 negative information respondents (62.0%) with P value = 0.015, Negative culture as much as 40 (56.3%) with P value = 0.016, Negative knowledge of 47 (66.3%) with P value = 0.039, Negative motivation as much as 42 (59%) with P value = 0.03, and positive behavior respondents as many as 53 respondents (74.6%). Conclusion: Based on the above results, there is a significant relationship between Information, Culture, Knowledge, and Motivation with Young Women's Behavior. It is expected to respondents to be able to always improve information on puberty and increase knowledge of changes in parilaku that occur.Keyword:Behavior, Information, Culture, Motivation and Knowledge